2017
DOI: 10.1113/jp275139
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine growth restriction results in persistent vascular mismatch in adulthood

Abstract: Maternal nutrient reduction induces intrauterine growth restriction (IUGR), increasing risks of chronic diseases later in life, including cardiovascular dysfunction. Using ultrasound, we determined regional blood flow, blood vessel sizes, and distensibility in IUGR baboons (8 males, 8 females, 8.8 years, similar to 35 human years) and controls (12 males, 12 females, 9.5 years). The measured blood vessels were larger in size in the males compared to females before but not after normalization to body surface are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 89 publications
1
29
0
Order By: Relevance
“…The nature of these postnatal changes fit with the fibrosis demonstrated in the article reviewed here and Muralimanoharan et al (2017). The pattern of vascular distribution observed in IUGR offspring is reminiscent of the changes that occur in fetuses challenged by hypoxia or undernutrition (Cohn et al 1974;Kuo et al 2018). Further studies are needed to determine the life course progression of the consequences of these programmed structural alterations.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…The nature of these postnatal changes fit with the fibrosis demonstrated in the article reviewed here and Muralimanoharan et al (2017). The pattern of vascular distribution observed in IUGR offspring is reminiscent of the changes that occur in fetuses challenged by hypoxia or undernutrition (Cohn et al 1974;Kuo et al 2018). Further studies are needed to determine the life course progression of the consequences of these programmed structural alterations.…”
supporting
confidence: 60%
“…At age ∼9 years (∼35 human years equivalent), IUGR baboons had smaller hindlimb but not brachial or common carotid arteries than controls and increased carotid blood flow velocity (Kuo et al . ). Overall these data indicate that region specific vascular and haemodynamic changes that occur with IUGR persist postnatally to and likely contribute to later life cardiac dysfunction.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Region‐specific vascular changes have been reported in IUGR newborns: the pattern of anomalies suggests a vascular redistribution effort in response to challenges in the perinatal period. Considering these data, differences in pulsatility and regional blood flow could have played a role in the abnormal development of the right clavicle in our IUGR patient.…”
Section: Discussionmentioning
confidence: 99%
“…4 The mechanical injury could otherwise be due to the role of a pulsating right subclavian artery, rather than interrupted formation of ossification centres as it has been demonstrated that the junction of these centres is actually more lateral. 5 Region-specific vascular changes have been reported in IUGR newborns 6 : the pattern of anomalies suggests a vascular redistribution effort in response to challenges in the perinatal period. Considering these data, differences in pulsatility and regional blood flow could have played a role in the abnormal development of the right clavicle in our IUGR patient.…”
Section: Discussionmentioning
confidence: 99%